Sequence of 71 nucleotides at the 3'-end of tobacco mosaic virus RNA. - Guilley, H (1975)
The sequence of the first 71 nucleotides from the 3'-OH end of tobacco mosaic virus RNA has been determined. After total T1 ribonuclease digestion of the viral RNA, the oligonucleotide C-C-C-A-OH, which originates from the 3'-OH terminus of the RNA, may be readily detected by electrophoresis at pH 2.5 or pH 3.0; it is the only oligonucleotide that migrates toward the cathode at these pHs. This property has been used to screen the purified products of partial T1 ribonuclease digestion of tobacco mosaic virus RNA for the fragment originating from the 3'-end of the native molecule. The sequence of nucleotides in the 3'-terminal fragment, identified in this manner, was determined by radiochemical methods. The fragment contained 71 nucleotides; no abnormal bases could be detected. Although it has been reported that the 3'-end of tobacco mosaic virus RNA is a substrate for aminoacylation by the histidyl-tRNA synthetase of yeast or Escherichia coli, we were unable to fold the sequence into the cloverleaf structure characteristic of tRNAs.